EFFECT OF TWO HARROWING SYSTEMS ON DECOMPOSITION OF ORGANIC MATTER, SOME SOIL PROPERTIES, GROWTH AND PRODUCTIVITY OF MAIZE - & Mageed, Nafawaah (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
A field experiment was conducted at Abu-Ghrib during 2013- 2014 season to study the effect of harrowing systems on the decomposition and fermentation on organic matter(OM) when added and mixed with the soil under special technology, as well as its effect on the growth parameters and productivity of (Zea mays L. 5018). The experiment was laid out using factorial randomized complete block design (RCBD) in split-split design with three replications in SCL bare soil with a percent of moisture ranged from 16 – 18 %. The main plots were designated to the two systems of harrowing (Rotary Harrowand Disc Harrow ). The sub main plots were specified for two organic matters ( Sheep manure ,cow manure ) . Data were statistically analyzed, and LSD was used to compare means at 0.05 levels. After 90 days, the obtained results indicated that there were significanteffects of harrowing systems on the rate of decomposition of organic matter and their effects on some soil and plant properties. The rotary harrows system showed significant increase in bulk density, and decrease in total porosity, average of mean weight diameter (MWD), total nitrogen, and height of plant. Under constant level of OM cow manure showed superiority on sheep manure and gave a significant increase in added nutrients, rate of decomposition of OM, improving soil properties and in turn on growth and productivity of Zea may L. 5018.